L’Euro-Amérique en question. - Olivier Compagnon (Centre de Recherches sur les Mondes Américains, 2009)
A classic topic in historiography, the cultural relations between Europe and Latin America have been the subject of many studies attesting to the existence of a common cultural area joining both sides of the Atlantic. These studies seem to indicate that the wind has always blown from East to West, the Latin American periphery bathing since the Modern Era in knowledge and practices from the European center. From an examination of the paradigms traditionally used to assess these Euro-American relations, and from the more recent notion of cultural transfer, this article explores the hypothesis of a role reversal in this traditional exchange, the hypothesis of a Latin America which exports knowledge and cultural practices to the rest of the world.